Effect of Short-Term Desiccation, Recovery Time, and CAPA–PVK Neuropeptide on the Immune System of the Burying Beetle Nicrophorus vespilloides - Urbański, Arkadiusz; Walkowiak-Nowicka, Karolina; Nowicki, Grzegorz; Chowański, Szymon; Rosiński, Grzegorz (Frontiers in Physiology, 2021)
Environmental conditions, especially related to winter, are crucial for shaping activity of insect immune system. However, our previous research clearly indicates differences in the immune system functioning when the cold stress was induced in the lab conditions and when the beetles were collected from natural environment during winter. This is probably related to the multiplication of observed effect by simultaneous presence of different stress factors characteristic for winter, including desiccation. For these reasons, our next step was analysis of the effects of short-term desiccation and recovery time on the functioning of immune system of burying beetle Nicrophorus vespilloides. Also, the effect of Tenmo-PVK-2 (Tenebrionid periviscerokinin), member of the CAPA-PVK neuropeptide family, was investigated to better understand observed changes. Short-term desiccation decreases the phagocytic activity of burying beetle haemocytes, which is correlated with a reduction in their adhesive ability. On the other hand, there was a significant increase in phenoloxidase (PO) activity and the level of proPO expression, which may suggest sealing the cuticula by melanin deposition and prevention of water loss. Additionally, the elevated level of defensin expression may be associated with the cross-talk between mechanisms which participate in insect response to environmental stress, including pathogen infection. After one hour of recovery time, the activity of tested cellular and humoral mechanisms mostly back to the control level. However, inhibition of the activity of PO and down-regulation of proPO were noted. These results also indicate importance of melanin deposition during water loss. Moreover, it suggests that some changes in immune system functioning during stress conditions do not have an immune function. Interestingly, part of the effects characteristic for recovery time were also observed after the application of Tenmo-PVK-2, mainly related to haemocytes morphology. These results indicate that CAPA-PVK neuropeptides may also influence on activity of burying beetle immune system. It should be also highlighted that, due to the study of the effects of CAPA-PVK neuropeptides, homologs of vertebrate neuromedin U, the results may be interesting for search evolutionary similarities in the functioning of the neuroendocrine system of insects and vertebrates.